EPIDEMIOLOGY AND PREVALENCE OF PARTIAL PRIMARY TOOTH AGENESIS IN CHILDREN ACROSS DIFFERENT AGE GROUPS (Ideal Journal of Multidisciplinary Research, 2026)
Partial primary tooth agenesis is a developmental anomaly characterized by the congenital absence of one or more teeth in the primary or permanent dentition. It represents one of the most common dental developmental disorders in pediatric populations and may significantly affect craniofacial growth, occlusion, mastication, speech, and psychosocial development. The aim of this study was to evaluate the prevalence of partial primary tooth agenesis among children of different age groups (0–18 years) and to analyze associated clinical patterns. A retrospective cross-sectional epidemiological study was conducted using dental records and panoramic radiographs of 1,250 pediatric patients. The prevalence, distribution by gender, localization patterns, and associations with other dental anomalies were assessed. The overall prevalence of partial tooth agenesis was 6.8%, with higher incidence in permanent dentition compared to primary dentition. The most frequently missing teeth were mandibular second premolars and maxillary lateral incisors. Agenesis was more common in females and often associated with microdontia and delayed eruption. The findings confirm that early diagnosis and age-based monitoring are essential for timely orthodontic and prosthetic planning.
Keywords: partial agenesis, primary dentition, pediatric dentistry, dental anomalies, prevalence, tooth development, epidemiology